Preparation and characteristics of carboxymethyl cellulose-based films embedding cinnamon essential oil and their application on mutton preservation - Han Wang; Peng Han; Yanghong Zhao; Lijuan Lu; Wenhui Qi; Kaixuan Zhao; Ying Shu; Zhisheng Zhang; Zhisheng Zhang (Frontiers in Nutrition)
Here, the cinnamon essential oil (CEO) was distributed evenly in the carboxymethyl cellulose (CMC) matrix, and an edible film was fabricated to improve its physicochemical properties and extend the shelf life of mutton. The results revealed that the film had high visible light transmittance, ultraviolet-blocking properties, and satisfactory mechanical. Incorporating CEO enhanced the antibacterial activity against Escherichia coli and Staphylococcus aureus. When the CEO concentration was 1.5 g/L, the oxygen permeability of the film was the lowest, and mechanical properties were the highest. When the CEO increased, the thickness of the films increased, and the moisture absorption and water solubility of the film decreased. Compared with mutton covered without film or with control film, the film containing CEO more significantly reduced pH value, total volatile basic nitrogen, thiobarbituric acid reactive substances, and total bacterial count of mutton samples, improved the color of the meat, and extended the shelf life of the mutton during the 12-day storage at 4°C. These results demonstrate the potential of the developed CMC-based film in preserving meat.